Derivation and validation of a prediction score for postoperative delirium in geriatric patients undergoing hip fracture surgery or hip arthroplasty - Shen, Jiawei; An, Youzhong; Jiang, Baoguo; Zhang, Peixun (Frontiers in Surgery, 2022)
INTRODUCTION: Postoperative delirium is a common complication of patients undergoing hip fracture surgery or arthroplasty, and is related to decreased survival time and physical function. In this study, we aim to build and validate a prediction score of postoperative delirium in geriatric patients undergoing hip fracture surgery or hip arthroplasty. METHODS: A retrospective cohort of geriatric patients that undergoing hip fracture surgery or hip arthroplasty was established. Variables of included patients were collected as candidate predictors of postoperative delirium. The Least Absolute Shrinkage and Selection Operator (LASSO) regression and logistic regression were used to derive a predictive score for postoperative delirium. The accuracy of the score was evaluated by the area under the curve (AUC) of receiver operating curves (ROC). We used bootstrapping resamples for model calibration. The prediction score was validated in an extra cohort. RESULTS: The incidence of postoperative delirium was 14.33% in the derivation cohort. 9 out of 40 variables were identified as predictors, including pre-operative delirium, cerebrovascular accident (CVA) with modified Rankin Scale, Diabetes with a random glucose level, Charlson Comorbidity Index (CCI), age, Application of benzodiazepines in surgery, surgical delay ≥2 days, creatine ≥90 umol/L, active smoker. The prediction score achieved a mean AUC of 0.848 in the derivation cohort, In the validation cohort, the mean AUC was 0.833. Besides, the prediction model was well-calibrated in the two cohorts. CONCLUSION: Based on the retrospective data, a prediction score for postoperative delirium in geriatric patients undergoing hip fracture surgery or hip arthroplasty was derived, the effectiveness of the score was validated in an extra cohort. The generalization ability of the score still needs to be tested in studies with more sufficient participants.